2004
DOI: 10.1165/rcmb.2003-0184oc
|View full text |Cite
|
Sign up to set email alerts
|

ATP Release Triggered by Activation of the Ca2+-Activated K+ Channel in Human Airway Calu-3 Cells

Abstract: Airway mucociliary clearance is subject to the autocrine/paracrine regulation of extracellular nucleotides released from the airway epithelial cells. The present study was performed in pursuit of effective modulators of ATP release under physiologic conditions in polarized human airway epithelial cells (Calu-3). Neither isoproterenol, forskolin, nor ionomycin augmented extracellular ATP release detected by luciferase assay. However, direct activation of the human intermediate conductance, Ca(2+)-activated K(+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…As has been shown in previous investigations, the cells responded to cAMP-related agents, such as FK (10 M, an adenylate cyclase activator), with anion secretion that reflects I SC changes ( Fig. 2A) (Devor et al, 1999;Ito et al, 2004a). Next, we examined the effects of H 2 O 2 on the subsequent I SC changes in response to FK.…”
Section: Bioelectric Responses To Apically and Basolaterallymentioning
confidence: 53%
See 1 more Smart Citation
“…As has been shown in previous investigations, the cells responded to cAMP-related agents, such as FK (10 M, an adenylate cyclase activator), with anion secretion that reflects I SC changes ( Fig. 2A) (Devor et al, 1999;Ito et al, 2004a). Next, we examined the effects of H 2 O 2 on the subsequent I SC changes in response to FK.…”
Section: Bioelectric Responses To Apically and Basolaterallymentioning
confidence: 53%
“…The airway epithelial cells secrete Cl Ϫ via NKCC1 in response to activation of human intermediate conductance Ca 2ϩ -activated K ϩ channels (KCNN4), so that anion secretion induced by 1-ethyl-2-benzimdazolinone (a KCNN4 activator) and thapsigargin (a cytosolic Ca 2ϩ mobilizing agent) is markedly inhibited by either bumetanide, a NKCC1 inhibitor, or ChTx, a KCNN4 channel blocker (Devor et al, 1999;Ito et al, 2004a,b). NKCC1 is also activated by cAMP/protein kinase A (PKA)-mediated phosphorylation (Haas and Forbush, 2000;Matthews, 2002); this mechanism fails to involve KCNN4 activation because of the lower sensitivity of ChTx to cAMP-mediated anion secretion (Ito et al, 2002(Ito et al, , 2004a. This was confirmed by the results shown in Fig.…”
Section: Effects Of H 2 O 2 On Airway Anion Secretion 299mentioning
confidence: 63%
“…Swelling-induced adenosine triphosphate (ATP) release has been widely reported in different cell types (Wang et al, 1996;Roman et al, 1999a,b;Sabirov et al, 2001;Shinozuka et al, 2001;Boudreault and Grygorczyk, 2002;Hisadome et al, 2002;Jans et al, 2002;Darby et al, 2003;van der Wijk et al, 2003;Evanko et al, 2004;Gatof et al, 2004;Ito et al, 2004;Ollivier et al, 2006), as well as in in vivo studies in rat cerebral cortex (Phillis and O'Regan, 2002;Phillis, 2004). However, controversy still exists about the mechanism of its release, which has been reported mediated by either exocytosis (Boudreault and Grygorczyk, 2002;van der Wijk et al, 2003;Gatof et al, 2004), a transporter (Roman et al, 1997;Braunstein et al, 2001Braunstein et al, , 2004Darby et al, 2003;Reigada and Mitchell, 2005), or a channel (Wang et al, 1996;Roman et al, 1999a;Sabirov et al, 2001;Hisadome et al, 2002;Ito et al, 2004;Okada et al, 2004;Sabirov and Okada, 2004).…”
Section: Swelling-induced Transmitter Releasementioning
confidence: 99%
“…Interestingly, direct activation of K Ca channels by 1-EBIO or chlorzoxazone appears to trigger a robust apical ATP release in Calu-3 cells (22). This mechanism may play a part in carbachol-induced ATP release since carbachol activates K Ca channels.…”
Section: Mixed Secretion Of Chloride and Bicarbonatementioning
confidence: 92%
“…Irokawa et al (20) suggested that the ratio of cell surface to apical lumen volume is 20 and 6,000 times greater in human submucosal gland tubules than in the "virtual gland" and Ussing chambers, respectively. The effect of released ATP is perhaps only evident when the apical lumen volume stays put and remains small (18,22,49).…”
Section: Mixed Secretion Of Chloride and Bicarbonatementioning
confidence: 99%